Absence of Proteoglycan 4 (Prg4) Leads to Increased Subchondral Bone Porosity Which Can Be Mitigated Through Intra‐Articular Injection of PRG4. Issue 10 (26th June 2019) - Abubacker, Saleem; Premnath, Priyatha; Shonak, Anchita; Leonard, Catherine; Shah, Sophia; Zhu, Ying; Jay, Gregory D.; Schmidt, Tannin A.; Boyd, Steven; Krawetz, Roman
ABSTRACT: Proteoglycan 4 (PRG4) is a mucin‐like glycoprotein important for joint health. Mice lacking Prg4 demonstrate degeneration of the cartilage and altered skeletal morphology. The purpose of this study was to examine if Prg4 deficiency leads to subchondral bone defects and if these defects could be mitigated through intra‐articular injection of recombinant human PRG4 (rhPRG4). Mice deficient in Prg4 expression demonstrated increased cartilage thickness and increased subchondral bone porosity compared with C57BL/6 controls. While the porosity of the subchondral bone of Prg4 −/− mice decreased over time with maturation, intra‐articular injection of rhPRG4 was able to forestall the increase in porosity. In contrast, neither hyaluronan (HA) nor methylprednisolone injections had beneficial effects on the subchondral bone porosity in the Prg4 knockout mice. Bone marrow progenitor cells from Prg4 −/− mice demonstrated reduced osteogenic differentiation capacity at 4 weeks of age, but not at 16 weeks of age. While most studies on PRG4/lubricin focus on the health of the cartilage, this study demonstrates that PRG4 plays a role in the maturation of the subchondral bone. Furthermore, increasing joint lubrication/viscosupplementation through injection of HA or controlling joint inflammation through injection of methylprednisolone may help maintain the cartilage surface, but had no positive effect on the subchondral bone in animals lacking Prg4 . Therefore, alterations in the subchondral bone in models with absent or diminished Prg4 expression should not be overlooked when investigating changes within the articular cartilage regarding the pathogenesis of osteoarthritis/arthrosis. © 2019 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 37:2077–2088, 2019